Competent blastocyst and receptivity endometrium improved clinical pregnancy in fresh embryo transfer cycles: a retrospective cohort study - Longmei Wang; Pingping Qiu; Lizhi Jiang; Ping Li; Yufei Jiang (BMC, 2024)
Abstract Background Embryo quality is usually regarded as a key predictor of successful implantation and clinical pregnancy potential. The identification of embryos that have the capacity to implant and result in a healthy pregnancy is a crucial part of in vitro fertilization (IVF). Usually, morphologically high-quality embryos are chosen for embryo transfer in IVF treatment. The aim of this study was to assess the association between the available blastocyst formation rate and the clinical pregnancy outcome following the first fresh embryo transfer cycle and provide systematic individual treatment to adjust endometrial receptivity for the next transfer cycle. Methods This retrospective, single-center study included 512 fresh embryo transfers conducted between 11/2019 and 08/2021, which consisted of 385 cleavage-stage (Day 3) and 127 blastocyst-stage (Day 5) embryo transfers. The two groups were divided into a clinical pregnancy group and a nonclinical pregnancy group for comparison. The association between the available blastocyst formation rate and the clinical pregnancy rate in the Day 3 and Day 5 transfer groups were considered. Results In the Day 3 group, there were 275 clinical pregnancies, and the clinical pregnancy rate was 71.43%. Although the two pronuclei (2PN) oocyte rate and available embryo rate at Day 3 were significantly higher in the clinical pregnancy group than the nonclinical pregnancy group (P < 0.05), the blastocyst formation rate and the available blastocyst formation rate were not significantly different between the clinical pregnancy group and the nonclinical pregnancy group (P > 0.05). In the Day 5 group, there were 81 clinical pregnancies, and the clinical pregnancy rate was 63.78%. No baseline characteristics showed any obvious differences between the clinical pregnancy group and nonclinical pregnancy group (P > 0.05). The blastocyst formation rate in the nonclinical pregnancy group was higher than that in the clinical pregnancy group, but the difference was not statistically significant (81.06% vs. 77.03%, P = 0.083). Interestingly, the available blastocyst formation rate and the Day 5 available blastocyst formation rate were significantly higher in the nonclinical pregnancy group than the clinical pregnancy group (66.19% vs. 60.79%, P = 0.014; 54.58% vs. 46.98%, P = 0.007). Conclusions In fresh cycles, the available blastocyst formation rate was not associated with the clinical pregnancy outcome for Day 3 embryo transfers, and the available blastocyst formation rate was not positively correlated with the clinical pregnancy outcome for Day 5 embryo transfers.